2020
DOI: 10.1111/jcmm.15950
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations of TCTN3/LTBP2 with cellular function changes in congenital heart disease associated with polydactyly

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…A large amount of evidence shows that genetic factors conduce to most CHD (Chen et al, 2017; Chen et al, 2020; Saliba et al, 2020; Zaidi & Brueckner, 2017). The promoter is a component of a gene that controls the onset and extent of gene expression, playing a key role in transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of evidence shows that genetic factors conduce to most CHD (Chen et al, 2017; Chen et al, 2020; Saliba et al, 2020; Zaidi & Brueckner, 2017). The promoter is a component of a gene that controls the onset and extent of gene expression, playing a key role in transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that RHD (Rh blood group D antigen) [154], S100A12 [155], TXN (thioredoxin) [156], TLR9 [157], S100P [158], TAGLN2 [159], S100A9 [160], CA1 [161], HP (haptoglobin) [162], RPL39 [163], F5 [164], PINK1 [165], B2M [166], S100A11 [167], SLC4A1 [168], CBS (cystathionine beta-synthase) [169], AHSP (alpha hemoglobin stabilizing protein) [170], F12 [171], EPHB4 [172], NFE2 [173], VRK1 [174], GPX1 [175], FOXA1 [176], CYP11B2 [177], NOX1 [178], IL33 [179], NPHS1 [180], OTC (ornithine transcarbamylase) [181], SULF1 [182], CYP1A1 [183], DCN (decorin) [184], ADAMTS7 [185], WNT4 [186], LAMA4 [187], SCN4A [188], CACNB2 [189], GNB3 [190], ENPEP (glutamyl aminopeptidase) [191], WNK4 [192], FOXC1 [193], PAX8 [194], ROBO1 [195], CXCL8 [196], PAPPA2 [197], LOX (lysyl oxidase) [198], NOSTRIN (nitric oxide synthase trafficking) [199], MUC16 [200], MIOX (myo-inositol oxygenase) [201], CYP11A1 [202] and CYP3A5 [203] are involved in the pregnancy complications. Modification in the activity and expression of RHD (Rh blood group D antigen) [204], S100A12 [205], TLR9 [206], ANXA3 [207], S100P [208], TAGLN2 [209], S100A9 [210], KCNH2 [211], HP (haptoglobin) [212], SELENBP1 [213], TANGO2 [214], PINK1 [215], TFR2 [216], B2M [217], LTBP2 [218], PGLYRP1 [219], HRH2 [220], CLEC5A [221], PLSCR4 [222], S100A11 [223], PPBP (pro-platelet basic protein) [224], RAP1GAP […”
Section: Discussionmentioning
confidence: 99%
“…HLA-DRA [148], SERPINA1 [149], ABHD12 [150], IMPA2 [151], ARSA (arylsulfatase A) [152], LRFN5 [153], PLXNA4 [154], CHL1 [155], ITPKB (inositol-trisphosphate 3-kinase B) [156], PTN (pleiotrophin) [157], LAMA2 [158], CDH6 [159] and A2M [160] have been shown to have an important role in neurological disorders, but these genes might be associated with progression of T2DM. HLA-F [161], HLA-H [162], FGA (fibrinogen alpha chain) [163], HSPA1B [164], MRC1 [165], DAB2IP [166], KCNJ8 [167], KLKB1 [168], CXCL2 [169], SERPINE2 [170], ADH1C [171], AMBP (alpha-1-microglobulin/bikunin precursor) [172], NR4A2 [173], TYMP (thymidine phosphorylase) [174], TFRC (transferrin receptor) [175], PLAU (plasminogen activator, urokinase) [176], COL6A2 [177], COL15A1 [178], ABI3BP [179], NEXN (nexilin F-actin binding protein) [180], S1PR1 [181], THY1 [182], COL4A1 [183], COL5A2 [184], ADAMTS2 [185], ECM1 [186] and LTBP2 [187] have been found to be differentially expressed in cardiovascular diseases, but these genes might be linked with progression of T2DM. CCL20 [188], CRH (corticotropin releasing hormone) [189], SPP1 [190], LDLR (low density lipoprotein receptor) [191], RORA (RAR related orphan receptor A) [192], LYZ (lysozyme) [193], PTPRN2 [194], DAPK2 [195], OIP5 [196], PON3 [197], NR4A3 [198], VCAN (versican) [199], CNTNAP2 [200], IL1RAP [201], GLI2 [202], CDH13 [203], AEBP1 [204], BGN (biglycan) [205], LOX (lysyl oxidase) [206], IL1RL1 [207] and LUM (lumican) [208] were found to be involved in advancement of obesity, but these genes might be key for development of T2DM.…”
Section: Discussionmentioning
confidence: 99%